Manajemen Program Tahfidz di SMP Al-Islam Kartasura - Zakariya, Aulif Angga; Suherman, Eman (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study aims to analyze the management of the Tahfidz Al-Qur’an program at SMP Al-Islam Kartasura through four management functions: planning, organizing, actuating, and evaluating. A descriptive qualitative method was employed, with data collected through interviews, observations, and documentation. The results indicate that SMP Al-Islam Kartasura has implemented procedural management functions, ranging from ambitious planning to an ideal teacher-student ratio (1:10–1:12). However, significant obstacles were found in the implementation and evaluation stages, such as the discrepancy between target demands and students' actual capacity, as well as a one-sided evaluation mechanism. To date, evaluation has focused primarily on students' administrative achievements, while systematic evaluation of teacher performance and teaching methods has not yet been implemented. The implications of this study emphasize the need for synchronized control between schools and parents, as well as the importance of internal evaluation for educators to improve the quality of the Tahfidz program sustainably.